2017
DOI: 10.1590/1809-4430-eng.agric.v37n2p257-267/2017
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Reference Evapotranspiration Through Continuous Probability Modelling

Abstract: ABSTRACT:This study aimed at testing the fit of continuous probability distributions to a daily reference evapotranspiration dataset (ET0) at a 75% probability level for designing of irrigation systems. Reference evapotranspiration was estimated by the Penman-Monteith method (FAO-56-PM) for eight locations, within the state of Espírito Santo (Brazil), where there are automatic gauge stations. The assessed probability distributions were beta, gamma, generalized extreme value (GEV), generalized logistic (GLO), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…In terms of the marginal structure, our results are consistent with other global-scale studies in literature (besides the ones previously mentioned in Section 2.2) on nearly Gaussian temperature [89], wind speed transition of extreme tail from Rayleigh to Weibull and Pareto-type [70,[170][171][172], sea level pressure [173], streamflow heavy tail [157,174], precipitation Pareto-type tail [3,74,149,[175][176][177][178][179][180][181][182], evaporation [183,184], and nearly Gaussian turbulent processes [185].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the marginal structure, our results are consistent with other global-scale studies in literature (besides the ones previously mentioned in Section 2.2) on nearly Gaussian temperature [89], wind speed transition of extreme tail from Rayleigh to Weibull and Pareto-type [70,[170][171][172], sea level pressure [173], streamflow heavy tail [157,174], precipitation Pareto-type tail [3,74,149,[175][176][177][178][179][180][181][182], evaporation [183,184], and nearly Gaussian turbulent processes [185].…”
Section: Discussionsupporting
confidence: 90%
“…Khanmo-hammadi [31] fitted annual reference evapotranspiration data to Lognormal, generalized logistic, and Pearson III distributions and realized that Pearson III was the most appropriate. Uliana et al [32] fitted evapotranspiration to Gamma distribution, which is a type of Pearson III distribution. Msowoya et al [33] fitted the evapotranspiration data to the generalized logistic distribution.…”
Section: Reference Evapotranspirationmentioning
confidence: 99%
“…Thus, it can be assumed that yðt, VÞ is a function of time t in years only, that is yðt, VÞ = yðtÞ. Under this assumption, we have ∂y m ðt, VÞ/∂t = dy m ðtÞ/dt so that the model in Equation [32] can be expressed as…”
Section: Maize Yield Modeling and Predictionmentioning
confidence: 99%
“…The most influential factor for climate change and the water cycle is evapotranspiration, as it is the only linkage between the water balance and the surface energy balance of the land (Wang et al, 2014). Some well-known authors worldwide suggested that knowledge about best fit statistical probability model in site ease is a correct hydrological prediction in the dimensioning drainage and irrigation planning (Fernandes, Wolff & Folegatti, 2019;Nam & Choi, 2014;Uliana et al, 2017;Yoo, Choi & Jang, 2008).…”
Section: Introductionmentioning
confidence: 99%